2008
DOI: 10.4322/tmm.00502009
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Da Incorporação De Fibras De Coco No Comportamento Dinâmico-Mecânico De Compósitos Com Matriz Poliéster

Abstract: ResumoRealizou-se um estudo da variação com a temperatura dos parâmetros dinâmico-mecânicos de compósitos com matriz poliéster incorporada com fibras de coco. Diferentes percentagens em peso de fibras de coco, até 40%, foram misturadas com resina poliéster ortoftálica e, após prensagem, curada por 24 horas à temperatura ambiente. Ensaios dinâmico-mecânicos (DMA) foram realizados para se obter os módulos de armazenamento e perda, bem como a tangente delta para cada tipo de compósito com diferentes quantidades d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
5
0
5
Order By: Relevance
“…The loss factor is associated to the damping characteristic of the material, and the balance between elastic and viscous phase. Performing average and standard deviation calculations in the loss factor results, it is noticed that these values are 5.4±0.4%, same values observed for polyester/coconut composites 19 at room temperature. Monteiro et al 19 also observed this effect and the authors associated this behavior to the fact that the coconut fiber supports partially the stress and some deformation of fiber/matrix interface.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The loss factor is associated to the damping characteristic of the material, and the balance between elastic and viscous phase. Performing average and standard deviation calculations in the loss factor results, it is noticed that these values are 5.4±0.4%, same values observed for polyester/coconut composites 19 at room temperature. Monteiro et al 19 also observed this effect and the authors associated this behavior to the fact that the coconut fiber supports partially the stress and some deformation of fiber/matrix interface.…”
Section: Resultsmentioning
confidence: 62%
“…Performing average and standard deviation calculations in the loss factor results, it is noticed that these values are 5.4±0.4%, same values observed for polyester/coconut composites 19 at room temperature. Monteiro et al 19 also observed this effect and the authors associated this behavior to the fact that the coconut fiber supports partially the stress and some deformation of fiber/matrix interface. In this way, the energy loss is related to the interaction between the matrix and the fibers, or, in other words, if the interface is more resistant, the energy dissipation is reduced.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Glass transition temperature was identified through tan δ peak in tan δ versus temperature curve. The E ′ value is directly related to the ability of the material to tolerate mechanical loads with recoverable strain and it is similar to flexural modulus 22. Conceptually, inorganic organic composites are often expected to become stiff and more brittle upon incorporation of inorganic fillers 11.…”
Section: Resultsmentioning
confidence: 99%
“…(8) A técnica de DMA permite não somente avaliar o comportamento viscoelástico como também determinar a região de transição vítrea de compósitos poliméricos. (9) O ensaio de DMA também fornece informações sobre o módulo elástico ou de armazenamento (E'), o módulo de dissipação viscosa ou módulo de perda (E'') e sobre o amortecimento mecânico ou atrito interno tan δ ) ' ' ' (tan E E = δ de um material quando sujeito a uma solicitação dinâmica. (8) Esses parâmetros indicam o nível de interação dinâmica entre a matriz polimérica e a fibra que foi incorporada.…”
Section: Introductionunclassified